Chitosan-starch cross-linked citric acid as adsorptive hemodialysis membrane. (2022) - Saiful; Mardiyana, Lidiya; Rahmi; Suhud, Khairi; Raharjo, Yanuardi
Abstract: The development and application of membrane methods in the medical field are essential to separate and eliminate toxins and impurities in the bloodstream through the process of hemodialysis. To be able to eliminate all toxic substances in the body fluid, the hemodialysis membrane must have the dual ability of adsorption properties and diffusion through the pore membrane. The chitosan-starch hemodialysis membrane un-crosslinked and cross-linked has been made to separate creatinine compounds with those with the dual ability to combine diffusion and adsorption from the membrane. Chitosan-binding starch membranes are made using citric acid as a cross-linking agent. Chitosan starch membrane uncross-linked has a clean water flux of 96 Lh −1 m −2, whereas chitosan-starch membrane cross-linked has 90 L h −1 m −2 clean water flux. Chitosan-starch membrane uncross-linked can remove creatinine of 11.89 mg/gram where the amount removed by adsorption reaches 8.66 mg/gram membrane. The chitosan-starch cross-linked membrane can remove creatinine 9.86 mg/gram membrane with the amount removed by adsorption reaching 5.14 mg/gram membrane. Chitosan-starch membranes have hemodialysis characteristics that are integrated with adsorption, where blood toxins are released in one step.